CONFIRMATORY FACTOR ANALYSIS OF THAI TOURIST’S DEMAND FOR ADVENTURE TOURISM IN NAKHON NAYOK PROVINCE - Pingkaew, Natthineeporn; Tanongpang, Wattana; Kaewdang, Pim-on; Khiewpana , Rattachapong; Chaloeyprach, Wannaya (Journal of Liberal Art of Rajamangala University of Technology Suvarnabhumi, 2025)
This article aimed to analyze and validate the structural model of second-order confirmatory factor analysis (CFA) concerning Thai tourists’ preferences for adventure tourism in Nakhon Nayok Province. A sample of 400 Thai tourists was selected through accidental sampling, with data collected via a structured questionnaire. The statistical tools employed for data analysis included descriptive statistics and second-order CFA. The research findings indicate that the analysis of the components of Thai tourists’ needs regarding adventure tourism in Nakhon Nayok Province revealed 19 variables across 4 components: accessibility, tourism activities, tourist attractions, and facilities. The aspects of tourism activities, tourist attractions, and facilities align with the conceptual framework and empirical data. The four components have weights ranging from 0.70 to 0.92, ranked from highest to lowest as follows: 1) Accessibility, 2) Tourism activities, 3) Tourist attractions, and 4) Facilities. The model’s components meet the statistical criteria and are significantly coherent (c2 2nd order= 61.046, df = 1.152, p-value = 0.209, CFI = 0.999, GFI = 0.984, AGFI = 0.943, RMSEA = 0.020). Therefore, this model can be applied to plan the development of adventure tourism in Nakhon Nayok Province.